2017
DOI: 10.1016/j.bbadis.2017.03.019
|View full text |Cite
|
Sign up to set email alerts
|

Dihydromyricetin prevents obesity-induced slow-twitch-fiber reduction partially via FLCN/FNIP1/AMPK pathway

Abstract: Obesity is often accompanied by decreases in the proportion of skeletal muscle slow-twitch fibers and insulin sensitivity. Increased plasma non-esterified fatty acids (NEFA) levels are responsible for obesity-associated insulin resistance. Palmitate, one of the most elevated plasma NEFA in obesity, has been recognized as the principle inducer of insulin resistance. The present study showed that increased plasma NEFA levels were negatively linked to slow-twitch fiber proportion and insulin sensitivity, while sl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 54 publications
2
34
0
Order By: Relevance
“…DM displays a broad range of biological and pharmacological activities such as antioxidant, anti-inflammatory, anti-tumor, neuroprotective and hepatoprotective effects [17][18][19][20][21]. Our previous studies demonstrated that DM could improve skeletal muscle insulin resistance and stimulate myokine secretion [22][23][24]. Importantly, we verified that DM could reverse mitochondrial dysfunction in skeletal muscle under acute hypoxic conditions, which contributes to improvements in physical performance [25].…”
Section: Introductionsupporting
confidence: 63%
“…DM displays a broad range of biological and pharmacological activities such as antioxidant, anti-inflammatory, anti-tumor, neuroprotective and hepatoprotective effects [17][18][19][20][21]. Our previous studies demonstrated that DM could improve skeletal muscle insulin resistance and stimulate myokine secretion [22][23][24]. Importantly, we verified that DM could reverse mitochondrial dysfunction in skeletal muscle under acute hypoxic conditions, which contributes to improvements in physical performance [25].…”
Section: Introductionsupporting
confidence: 63%
“…In this study, we showed that leucine significantly increased the activities of MDH and SDH in porcine skeletal muscle satellite cells. Sirt1 and AMPK play a key role in fiber‐type specification (Chalkiadaki, Igarashi, Nasamu, Knezevic, & Guarente, ; Zhou et al., ). In this study, we showed that leucine significantly increased the protein levels of Sirt1 and phospho‐AMPK.…”
Section: Discussionmentioning
confidence: 99%
“…The determination of mitochondrial DNA copy number was performed as described previously [52]. Briefly, mtDNA was extracted from soleus muscles and C2C12 myotubes using the Mito DNA Extraction Kit (Genmed Scientifics Inc., Wilmington, MD, USA) according to the manufacturer's instructions.…”
Section: Determination Of Mitochondrial Dna Copy Numbermentioning
confidence: 99%